2018
DOI: 10.1002/ss.20266
|View full text |Cite
|
Sign up to set email alerts
|

Neoliberal Capitalism and Racism in College Athletics: Critical Approaches for Supporting Student‐Athletes

Abstract: This chapter highlights issues of racism and neoliberal capitalism that exist within the market‐like structure of intercollegiate athletics on college campuses, as well as some of the consequences for student‐athletes. We discuss the importance of using critical frameworks to better understand and shift the culture and structure of athletic programs to be more inclusive and supportive of the needs and interests of college athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…Some of those outcomes are within their identity development, academic performance, and choice of major/ discipline. A substantial amount of focus toward the athletic identity is due to the neoliberal capitalism that is prevalent in the collegiate athletic model, which often presents consequences for the student-athletes (Gaston-Gayles et al, 2018). Likewise, with stereotypes surrounding the student-athletes, their mere association with athletic identity impacts outcomes as previously noted.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Some of those outcomes are within their identity development, academic performance, and choice of major/ discipline. A substantial amount of focus toward the athletic identity is due to the neoliberal capitalism that is prevalent in the collegiate athletic model, which often presents consequences for the student-athletes (Gaston-Gayles et al, 2018). Likewise, with stereotypes surrounding the student-athletes, their mere association with athletic identity impacts outcomes as previously noted.…”
Section: Discussionmentioning
confidence: 96%
“…When the conflicting roles (i.e., student and athlete) are in harmony, less conflict occurs (Killeya-Jones, 2005). However, the businesslike nature of college athletics places an extreme amount of attention to a model that glorifies athletic pursuits over other interests (Gaston-Gayles et al, 2018). Thus, one solution to balancing the identities of student-athletes is to mandate that coaches create more flexibility within their players' schedules (Cooper, 2016;Killeya-Jones, 2005).…”
Section: Identity Foreclosurementioning
confidence: 99%
“…For example, the reference to the negative impact of scheduling on student-athletes' academic performance underscore the belief that athletics was overemphasized. In addition to scheduling, additional aspects of the neoliberalism athletics sub-culture (Gayles et al, 2018) included recruiting tactics, coaches' salaries, and monies spent on athletic facilities arms race were highlighted by the faculty participants. The emotional dimension was illustrated when faculty contrasted the treatment of high-profile sports such as football and basketball (e.g., scheduling for TV broadcasting purposes, preferential treatment with course enrollment, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the benefits associated with the NCAA and its commercialized institutional logics (Southall & Nagel, 2010), not all faculty have embraced the integrated view/collegiate model of athletics promulgated by former President Myles Brand (Cooper et al, 2017;Sack, 2009). During the late 1980s and early 1990s, several faculty-led academic reform movements were established to counteract the prevailing trend of neoliberal capitalism at big-time college sport institutions (Gayles, Comeaux, Ofoegu, & Grummert, 2018). KCIA is one of the most visible among these reform groups.…”
Section: College Sport Reform Efforts and Faculty Perspectivesmentioning
confidence: 99%
“…The economic realities of 21 st century commercial college athletics, particularly football and men's basketball, no longer justify strict restriction of student-athlete compensation. In fact, some have suggested that the NCAA failing to compensate student-athletes stems from neoliberal and racist ideologies deeply rooted in NCAA host institutions (Gales, Comeaux, Ofoegbu, & Grummert, 2018). These researchers suggested that the NCAA is the commercial enterprise solely reaping the benefits of student-athlete exploitation.…”
Section: Literature Reviewmentioning
confidence: 99%